ANALISIS PELAKSANAAN STRATEGI DISTRIBUSI FISIK PRODUK HANDPHONE SMARTFREN - Rahayu, Sherly; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
In an economy that has been advanced, the manufacturers do not sell their products directly to the end user. Many options can be used to distribute goods and also to the buyer. A company may distribute goods directly to consumers though is quite large, while other companies distribute their products through intermediaries. And not a few companies that use some combination of distribution channels to reach different market segments .A competition for the company can be an opportunity to develop the company's business and can be a threat to the company. Therefore, the management company is required to always be responsive in adapting to environmental changes that continue to occur and have an influence on economic enterprise. The company should have a strategy to excel in the market. This research was conducted at PT. Prima Sejahtera Barelang Pekanbaru located at HR.Soebrantas No. 89. This study aims to determine the distribution strategy undertaken by PT. Prima Sejahtera Barelang Pekanbaru to increase sales volume.Keywords: Distribution, Strategy, Sales, Management, Marketing